2021
DOI: 10.3390/en14123593
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characteristics of Preliminary Shutdown and Startup Sequences for a Model Counter-Rotating Pump-Turbine

Abstract: Pumped Hydropower Storage (PHS) is the maturest and most economically viable technology for storing energy and regulating the electrical grid on a large scale. Due to the growing amount of intermittent renewable energy sources, the necessity of maintaining grid stability increases. Most PHS facilities today require a geographical topology with large differences in elevation. The ALPHEUS H2020 EU project has the aim to develop PHS for flat geographical topologies. The present study was concerned with the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The comparison is based on the results of the high-fidelity model. The methodology and boundaries used for the CFD simulations are described in further detail by Fahlbeck et al (2021) and Fahlbeck et al (2022a).…”
Section: Methodology and System Propertiesmentioning
confidence: 99%
“…The comparison is based on the results of the high-fidelity model. The methodology and boundaries used for the CFD simulations are described in further detail by Fahlbeck et al (2021) and Fahlbeck et al (2022a).…”
Section: Methodology and System Propertiesmentioning
confidence: 99%
“…With the current design, the torque of the bevel gears is not to exceed 250 N•m according to the test facility at TU Braunschweig. Our earlier studies of a similar CRPT showed that large force and torque spikes are to be expected during the startup procedure in pump-mode if not handled with care [13]. These torque spikes can easily exceed the torque at the final operating point and must thus be limited.…”
Section: The Contra-rotating Pump-turbinementioning
confidence: 99%
“…Many of these studies lack an analysis of how the CRPT behaves at time-varying load conditions and mode switching between pump and turbine. Our recent studies show that the runners of the CRPT can experience rapid and large load variations during shutdown and startup procedures in pump-mode, where the startup seems to be the most crucial [13].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 9 studied the variation process of pulsating pressure in runner area during start-up process based on 1D-3D coupling models. Fahlbeck et al 10 analyzed the flow characteristics under emergency shutdown and start-up condition. Liu 11 and Sabri et al 12 proposed that flow separation may occur at the runner blades under the case of no-load instability.…”
Section: Introductionmentioning
confidence: 99%